Pakoštane – Crkvina, the final resting place on the shores of Lake Vrana (In situ, 2025)
After a break of several years, research at the Crkvina site in Pakoštane on the shores of Lake Vrana resumed in the spring of 2024. This year's research campaign focused on the room next to the southern nave of the church, where a number of graves with numerous deceased persons were explored under the paving layer.
Keywords: Pakoštane; Crkvina; Middle Ages; cemetery; graves